Supply chain strategies in an era of natural resource scarcity - Kalaitzi, Dimitra; Matopoulos, Aristides; Bourlakis, Michael; Tate, Wendy (My University, 2018)
Purpose: The purpose of this paper is to explore the implications of natural resource scarcity (NRS) for companies’ supply chain strategies. Design/methodology/approach: Drawing on the resource dependence theory (RDT), a conceptual model is developed and validated through the means of exploratory research. The empirical work includes the assessment of qualitative data collected via 22 interviews representing six large multinational companies from the manufacturing sector. Findings: When the resources are scarce and vitally important, companies use buffering strategies. Buffering and bridging strategies are preferred when there are a few alternative suppliers for the specific resource and when there is limited access to scarce natural resources. Research limitations/implications: The research focuses on large multinational manufacturing companies so results may not be generalised to other sectors and to small- and medium-sized firms. Future research needs to examine the implications of NRS for organisational performance. Practical implications: This research provides direction to manufacturing companies for adopting the best supply chain strategy to cope with NRS. Originality/value: This paper adds to the body of knowledge by providing new data and empirical insights into the issue of NRS in supply chains. The RDT has not been previously employed in this context. Past studies are mainly conceptual and, thus, the value of this paper comes from using a qualitative approach on gaining in-depth insights into supply chain-related NRS strategies and its antecedents.
Keywords: Case studies; Risk Management; Qualitative data analysis; Supply chain strategy; Natural resource scarcity